2020
DOI: 10.3389/fnbeh.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Right Temporoparietal Junction Modulates In-Group Bias in Facial Emotional Mimicry: A tDCS Study

Abstract: The present study employs transcranial direct current stimulation (tDCS), a non-invasive brain stimulation technique, to explore the possible role of the right temporoparietal junction (rTPJ) in regulating in-group bias in facial emotional mimicry. Participants received either anodal or cathodal stimulation, or they were assigned to a sham condition. After that, they passively viewed a series of video clips depicting different emotions (happiness and anger) that were performed either by ethnic in-group or out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 63 publications
5
13
0
Order By: Relevance
“…Experiment 1 reveals that enhanced cortical excitability over the rTPJ does not improve emotional mimicry. This finding aids the interpretation of our prior research (Peng et al, 2020 ) by ruling out the possibility that the rTPJ regulates facial mimicry toward different emotions. Many previous studies attempting to explore the neural bases for emotional mimicry have demonstrated that both the classical MNS and extended MNS are engaged in emotional mimicry, with the former linked to motor stimulation and the latter linked to the process of affective expressions (Likowski et al, 2012 ; Rymarczyk et al, 2018 , 2019 ).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Experiment 1 reveals that enhanced cortical excitability over the rTPJ does not improve emotional mimicry. This finding aids the interpretation of our prior research (Peng et al, 2020 ) by ruling out the possibility that the rTPJ regulates facial mimicry toward different emotions. Many previous studies attempting to explore the neural bases for emotional mimicry have demonstrated that both the classical MNS and extended MNS are engaged in emotional mimicry, with the former linked to motor stimulation and the latter linked to the process of affective expressions (Likowski et al, 2012 ; Rymarczyk et al, 2018 , 2019 ).…”
Section: Discussionsupporting
confidence: 83%
“…As reviewed earlier, although our prior study (Peng et al, 2020 ) revealed alteration in rTPJ activity resulted in change of facial mimicry toward ethnic ingroup and outgroup expressions, it left an open question what the precise role rTPJ exerted in this modulation. The present study aimed to tap this issue by testing the two possible explanations via two experiments.…”
Section: Overview Of the Present Studymentioning
confidence: 89%
See 3 more Smart Citations